The genome sequence of the blue-tailed damselfly, Ischnura elegans (Vander Linden, 1820) [version 1; peer review: 2 approved] - Benjamin W. Price; Stephen J. Brooks; Martin Winter (Wellcome Open Research, 2022)
We present a genome assembly from an individual female Ischnura elegans (the blue-tailed damselfly; Arthropoda; Insecta; Odonata; Coenagrionidae). The genome sequence is 1,723 megabases in span. The majority of the assembly (99.55%) is scaffolded into 14 chromosomal pseudomolecules, with the X sex chromosome assembled.